RESPONSIBILITY AND EMOTIONAL BURNOUT OF TEACHERS - Olena Ivanivna Halian (Insight: the psychological dimensions of society, 2019)
Purpose. The purpose of the publication is to analyze the results of an empirical study of the relationship between responsibility and emotional burnout of teachers.Methods. The expert judgment method has been used to assess the level of responsibility. The experts were representatives of the school administration, colleagues and parents, who had been offered a standard form describing the extreme manifestations of responsible and irresponsible behavior of teachers. To study the emotional burnout of teachers with different levels of responsibility, the methodology «Diagnosis of emotional burnout of personality» by V. Boyko and the questionnaire «Self-esteem of emotional well-being» (author I. Sedov) were used. Since we assumed a direct correlation between emotional burnout and personality traits such as anxiety and emotionality, we used the FPI Personal Questionnaire (G. Eysenk) to diagnose emotionality, and the parameters of situational and personal anxiety were diagnosed by determinants of «Methods for assessing the anxiety of C. Spielberger and Y. Hanin». Differences between groups of subjects with diferent levels of responsibility were determined using the Student's t-test.Results. It has been established that the process of formation of emotional burnout syndrome has an individual character and is determined by external (conditions of professional activity) and internal (individual characteristics of personality) determinants. Teachers with up to 6 years of experience, with both high and low levels of responsibility, have not found a symptom of emotional burnout. Educators with more than ten years of experience are characterized by several symptoms associated with experiencing and inappropriately responding to psycho-traumatic circumstances. Symptoms caused by occupational deformity are at the stage of formation. It has been shown that the emotional burnout syndrome is most intensively formed in highly responsible teachers.Conclusions. Therefore, emotional burnout syndrome is one aspect of self-control that is based on the observance of rules that are valuable to the individual, which makes one feel morally, mentally and physically exhausted. The generalizations made about the dependence of emotional burnout on responsibility prompt one to think about the subjective, individual nature of its development. The basic conditions of the (emotional burnout) deployment are the working conditions and the content of the motivational and semantic component of the personality